Neuropsychological Profiles of Children Following Vitamin B12 Deficiency During Infancy: A Case Series. Issue 3 (11th April 2016) - Greenham, M.; Anderson, V.; Campbell, J.; Monagle, P.; Beauchamp, M.H.
Abstract : Previous studies investigating long-term outcomes in children following vitamin B12 deficiency during infancy have been limited to IQ or clinical observation. This paper seeks to describe comprehensive neuropsychological profiles in a case series of school-aged children who were treated for infantile vitamin B12 deficiency. This was a retrospective case series of seven children who were treated for vitamin B12 deficiency during infancy and aged 5 to 16 years at the time of testing. While most children had age-expected intellectual performance, the distribution of the sample was skewed to the lower end of the normal range. Furthermore, children were found to have impairments in a number of neuropsychological domains, most common were attention and memory, followed by executive function. These results suggest that while neurological symptoms quickly resolve following treatment, these effects on early brain development may disrupt brain maturation and have the potential to impact on later development.